The causal relationship between digital literacy and students’ academic achievement: a meta-analysis - Feng Li; Liang Cheng; Xi Wang; Lingxia Shen; Yuxin Ma; A. Y. M. Atiquil Islam (Humanities & Social Sciences Communications)
Abstract This meta-analysis focuses on the relationship between digital literacy (DL) and academic achievement. The 35 independent effect sizes that were collected were analyzed using Comprehensive Meta-analysis (CMA) software version 2.0, and the results showed a significant, medium positive correlation between DL and academic achievement. In addition, there were significant differences in the correlation between DL and academic achievement among students of different grade levels, orientations of DL, subjects, sampling methods, and genders. We suggest that (1) schools should develop students’ DL by strengthening the construction of a digital learning environment; (2) teachers and parents should give more guidance to primary and middle school students on the application of digital tools, making them aware of the advantages and disadvantages of digital technology for learning; and (3) students should have general digital operation skills and further master the special methods and learning models of digital technology applied to different subjects. Finally, although the relationship between DL and academic achievement was moderated by gender, with a stronger link observed in males than females, there are no full gender ratios of participants from the samples. Therefore, the relationship between DL and achievement across genders needs to be further verified in future research.